Financing housing improvements in slum communities in Ghana: the case of the Kumasi Metropolis - López, Karen Tatiana Montiel (2011)
A Thesis Submitted to the Department of Planning Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the degree of Master of Science in Development Planning and Management.